Core and filamentary damage of fused silica induced by nanosecond laser at 1064 nm. (1st January 2023) - Zhang, Fawang; Wang, Biyi; Liu, Xinyi; Xu, Man; Liu, Hufeng; Miao, Xinxiang; Lü, Tao; Qiu, Rong; Guo, Decheng; Zhou, Qiang; Jiang, Yong
Abstract: The behavior of 1064 nm laser-induced bulk damage (including core damage and filamentary damage) of fused silica was studied using a time-resolved pump-probe shadowgraph technique. The results indicate that the enhancement of incident laser energy only affects the area and location of core damage and the length of filamentary damage, while the diameter and the rightmost position of the filament are not affected. Based on the self-focusing effect and the temporal profile of the laser pulse, a discrete focus hypothesis is proposed, which can effectively elaborate the damage process.